Should we prescribe abstinence or wine once a day with supper in diabetes and prediabetes? - Kristian Rett (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
The ultimate goal of diabetes management is to minimize complications and maintain quality of life in the context of comprehensive cardiovascular risk management and patient-centered care. This includes lifestyle management and diabetes self-management education and support. In contrast to current pharmacological guidelines, which are patient-centered and evidence based, lifestyle guidelines still carry potential for improvement. Despite current best evidence from prospective controlled trials showing, that moderate wine consumption is associated with survival benefit, reduced risk of cardiovascular endpoints in both subjects with and without diabetes as well as reduced diabetes incidence in the context of the mediterranean diet, translation into clinical practice is unsatisfactory. Patients with diabetes and prediabetes need balanced and accurate information so they can make informed decisions about the risk-benefit balance of the traditional mediterranean drinking pattern and translate it into their personal lifestyle and diabetes self-management - if applicable and suitable. In this regard, balanced analysis of the available evidence as a counterbalance to notorious myths is necessary. This requires consideration of the broader context of european art of living, of direct and indirect effects of ethanol on glucose and lipid metabolism, distinction between harmful (binge drinking) and beneficial (regular with meals) drinking patterns, distinction between distilled (spirits) and fermented (wine and beer) beverages, appreciation of the phenomenon of dose-dependent effect reversal (hormesis or J-curve), which is common to all alcoholic beverages and finally respect of ethnical and regional as well as gender- and age-related differences.